OTH-003 Paediatric crohn's disease patients in remission have a reduced skeletal muscle protein balance after feeding. (8th June 2018) - Moran, Gordon; Walker, Amanda; Nixon, Aline; Devadason, David; Muhammed, Rafeeq; Tsintzas, Kostas; Kirkham, Sian; Stephens, Francis
Abstract : Introduction: Sarcopenia is common in active Crohn's disease (CD) and still prevalent in remission. This can lead to fatigue, physical inactivity and poor quality of life but the aetiology is unclear. We aimed to investigate the association between sarcopenia and anabolic resistance (AR) and insulin resistance (IR), and the role of physical activity in age, gender matched children with CD. Methods: 18 fasted, male and female CD (on thiopurines±anti-TNFα) in deep remission (16 y, BMI=21) and 9 matched controls (Con) (16 y, BMI=21) drank a liquid meal (Ensure plus, 44 g CHO, 14 g PRO, 11 g fat) at t=0. Arterialised hand and venous forearm blood samples were collected concurrently and brachial artery blood flow measured at baseline and every 20 mins for 2 hours. Net balance of branched chain amino acids (BCAA) and glucose were derived, giving indices of skeletal muscle protein balance and IR. Subjects had a DEXA scan and handgrip dynamometer test on the day, and wore a pedometer and completed a food diary (for 3 days) to assess physical activity and food intake. Patient questionnaires (incl. IBD-fatigue) were completed. Results: Net BCAA balance across the whole 2 hours was lower in CD vs Con (−0.1±0.2μmol/min vs 0.6±0.3μmol/min, p=0.05). Yet an initial response to feeding (t=0 to t=20) was exhibited by both CD (+1μmol/min) and Con (+0.8μmol/min) but was only sustained post 40 mins in Con. IBD-fatigue scores indicated CD had moderate fatigue (6), which had a moderate effect on daily activities (17). Handgrip dynamometer testing showed a trend towards greater fatigue in CD vs Con (+8%pts) in the dominant arm (p=0.061). A trend towards lower total body lean mass in CD (−15%, p=0.084) was found. No differences were detected in strength, physical activity, diet or IR. Thus despite not exhibiting AR (initial response to the meal) CD could not maintain a positive protein balance post feeding. This was associated with reduced muscle mass and function. Conclusions: The inability to sustain a positive protein balance postprandially could provide an explanation for the reduced muscle mass seen in CD patients in remission and be contributing to fatigue and poor muscle function. Pharmacological interventions to reduce protein breakdown and a high protein diet and /or exercise to improve anabolic response could be investigated as potential treatments.